The Potential Antibacterial Effect of Papaya Leaf Extract (Carica papaya L) and Miana Leaf Extract (Coleus scutellarioides L) as Adjuvant Therapy for Rifampicin-Resistant Tuberculosis - Wawan Sofwan Zaini; Nining Kurniati; Khayan Khayan; Bagus Muhammad Ihsan; Widyana Lakshmi Puspita; Muhammad Ifham Hanif (Poltekkes Kemenkes Palu, 2023)
The adhesion of Rifampicin-resistant TB to neutrophils plays an essential role in colonization. Several active compounds in papaya leaf and Miana leaf (Coleus scutellarioides L) are believed to regulate or prevent the formation of bacterial colonies. The purpose of this study was to determine the anti-bacterial effectiveness of extracts of papaya leaf (Carica Papaya L.) and Miana leaf (Coleus scutellarioides L) against bacterial isolates of Rifampicin-Resistant TB strain (RR). This research method is a in vitro laboratory experiment, and extracts of papaya leaf and Miana leaf (50, 25, 12,5%) were tested as anti-bacterial using the M-TB susceptibility test using the Proportion Method. The results showed the anti-bacterial ability of papaya leaf extract against bacterial isolates of the MTBC-Resistant Rifampicin strain at a concentration of 50% with a resistance percentage value of 0% so that it was included in the Sensitive category, but at a concentration of 25% the resistance percentage value was 42.86% % and a concentration of 12.5%, the percentage value of resistance is 42.86% so that it is included in the category of resistance (Resistant > 1% and Sensitive < 1%). The anti-bacterial ability of miana leaf extract against bacterial isolates of the MTBC-Resistant Rifampicin strain at a concentration of 50% with a resistance percentage value of 5.33%, at a concentration of 25%, with a resistance percentage value of 17.14%, and at a concentration of 12.5%, with a resistance percentage value of 100%, so all are included in the resistant category. The Conclusion 50% papaya leaf extract inhibits the formation of Rifampicin-resistant MTBC-resistant bacterial colonies, allowing its usage as a substitute ingredient in Rifampicin-resistant MTBC-resistant medications.